The pathophysiology of intestinal lipoprotein production - Giammanco, Antonina; Cefalù, Angelo B.; Noto, Davide; Averna, Maurizio R. (Frontiers in Physiology, 2015)
Intestinal lipoprotein production is a multistep process, essential for the absorption of dietary fats and fat-soluble vitamins. Chylomicron assembly begins in the endoplasmic reticulum with the formation of primordial, phospholipids-rich particles that are then transported to the Golgi for secretion. Several classes of transporters play a role in the selective uptake and/or export of lipids through the villus enterocytes. Once secreted in the lymph stream, triglyceride-rich lipoproteins (TRLs) are metabolized by Lipoprotein lipase (LPL), which catalyzes the hydrolysis of triacylglycerols of very low density lipoproteins (VLDLs) and chylomicrons, thereby delivering free fatty acids to various tissues. Genetic mutations in the genes codifying for these proteins are responsible of different inherited disorders affecting chylomicron metabolism. This review focuses on the molecular pathways that modulate the uptake and the transport of lipoproteins of intestinal origin and it will highlight recent findings on TRLs assembly.